PENGARUH PERBANDINGAN TEPUNG TALAS, TAPIOKA, DENGAN TEPUNG MOCAF DAN PERSENTASE TERHADAP MUTU KERIPIK TEMPE INOVASI (The Effect of Ratio of Taro Flour, Tapioca, and Mocaf Flour and Percentage of Laru on The Quality of Inovation Tempeh Chips) - Ika Octariyani Safitri; Herla Rusmarilin; Ridwansyah Ridwansyah (Universitas Sumatera Utara, 2017)
ABSTRACT The aim of this research was to find the effect of ratio of taro flour, tapioca, and mocaf flour and concentration of Yeast on the quality of innovation tempeh chips. This research was conducted at Laboratory of Food Technology and , Faculty of Agriculture, University of Sumatera Utara, Medan, using completely randomized design with two factors, i.e ratio of taro flour, tapioca, and mocaf flour (I) : (50%:40%:10% ; 40%:50%:10% ; 30%:60%:10% ; 20%:70%:10%) and concentration of Yeast (K) : (0,5% ; 1% ; 1,5% ; 2%). The parameters analyzed were water content, ash content, protein content, fat content, fiber content, carbohydrate content, oil absorption index, texture value and the organoleptic test of color, flavor, taste, and texture. The results showed that the ratio of taro flour, tapioca, and mocaf flour had highly significant effect on value of water content, ash content, fat content, fiber content, carbohydrate content, oil absorption index, texture value, and organoleptic color fresh tempeh, and did not differ significantly on protein content, the organoleptic test value of color tempeh chips, the organoleptic test value of flavor of fresh tempeh, the organoleptic test value of flavor of tempeh chips, the organoleptic test value of taste of tempeh chips, the organoleptic test value of texture of fresh tempeh. Concentration of Yeasthad highly significant effect on ash content, fiber content, carbohydrate content, and texture value, and did not differ significantly on water content, protein content, fat content, oil absorption index, the organoleptic test value of color of fresh tempeh, the organoleptic test value of color of tempeh chips, the organoleptic test value of flavor of fresh tempeh, the organoleptic test value of flavor of tempeh chips, the organoleptic test value of taste of tempeh chips, the organoleptic test value of texture of fresh tempeh. The interaction between the two factors had highly significant effect on ash content and fiber content, and did not differ significantly on water content, protein content, fat content, carbohydrate content, oil absorption index, texture value and the organoleptic test of color, flavor, taste, and texture. Fresh tempeh that had the best quality was at ratio of taro flour, tapioca, and mocaf flour of 20%:70%:10% and Concentration of Yeast1,5% and 2%. Antioxidant activity of fresh tempeh with the best quality was analyzed. Keyword : taro flour, tapioca, mocaf flour, yeast ABSTRAK Penelitian ini dilakukan untuk mengetahui Pengaruh perbandingan tepung talas, tapioka, dengan tepung mocaf dan jumlah laru terhadap mutu keripik tempe inovasi. Penelitian ini dilakukan di Laboratorium Teknologi Pangan, Fakultas Pertanian, Universitas Sumatera Utara, menggunakan rancangan acak lengkap faktorial 2 faktor, yaitu perbandingan tepung talas, tapioka, dan tepung mocaf (I) (50%:40%:10% ; 40%:50%:10% ; 30%:60%:10% ; 20%:70%:10%) dan jumlah laru (K) (0,5%, 1%, 1,5%, 2%). Parameter yang dianalisa adalah kadar air, kadar abu, kadar protein, kadar lemak, kadar serat, kadar karbohidrat, daya serap minyak, uji tekstur, nilai organoleptik warna, aroma, rasa, dan tekstur. Hasil penelitian menunjukkan bahwa perbandingan tepung talas, tapioka, dan tepung mocaf memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar abu, kadar lemak, kadar serat, kadar karbohidrat, daya serap minyak, uji tekstur, nilai hedonik warna tempe segar, namun memberikan pengaruh berbeda tidak nyata terhadap kadar protein, nilai hedonik warna keripik tempe, nilai hedonik aroma tempe segar, nilai hedonik aroma keripik tempe, nilai hedonik rasa keripik tempe, dan nilai hedonik tekstur tempe segar. Jumlah laru memberikan pengaruh sangat nyata terhadap kadar abu, kadar serat, kadar karbohidrat, dan uji tekstur, namun memberikan pengaruh berbeda tidak nyata terhadap kadar air, kadar protein, kadar lemak, daya serap minyak, nilai hedonik warna tempe segar, nilai hedonik warna keripik tempe, nilai hedonik aroma tempe segar, nilai hedonik aroma keripik tempe, nilai hedonik rasa keripik tempe, dan nilai hedonik tekstur tempe segar. Interaksi keduanya memberikan pengaruh berbeda sangat nyata terhadap kadar abu dan kadar serat, namun memberikan pengaruh berbeda tidak nyata terhadap kadar air, kadar protein, kadar lemak, kadar karbohidrat, daya serap minyak, uji tekstur, nilai organoleptik warna, aroma, rasa, dan tekstur. Perlakuan tempe segar terbaik terdapat pada perbandingan tepung talas, tapioka dan tepung mocaf 20%:70%:10% dan jumlah laru 1,5% dan 2%. Perlakuan tempe segar terbaik diuji aktivitas antioksidannya. Kata Kunci : laru, tapioka, tepung mocaf, tepung talas.